2020
DOI: 10.3892/ijo.2020.5003
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic activation of FOXF1 confers cancer stem cell properties to cisplatin‑resistant non‑small cell lung cancer

Abstract: The underlying molecular mechanisms of cisplatin resistance in non-small cell lung cancer (NSCLC) are unclear. In this study, a novel differential methylation region located in the upstream regulatory region of the forkhead box F1 (FOXF1) gene was identified. The abnormal hypomethylation of FOXF1 increased the expression of FOXF1, and the high expression of FOXF1 promoted cell proliferation and inhibited cell apoptosis induced by cisplatin, which resulted in cisplatin resistance in NSCLC cells. In addition, FO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
(38 reference statements)
0
9
0
Order By: Relevance
“…Foxf1 is a member of the forkhead box family of transcription factor and has been previous reported to be critical for multiple human cancer, such as colorectal cancer [27], gastrointestinal stromal tumor [28] breast cancer [29,30] and non-small cell lung cancer [31]. we found that the downregulation of Foxf1 was signi cantly correlated with a poorer prognosis for patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 49%
“…Foxf1 is a member of the forkhead box family of transcription factor and has been previous reported to be critical for multiple human cancer, such as colorectal cancer [27], gastrointestinal stromal tumor [28] breast cancer [29,30] and non-small cell lung cancer [31]. we found that the downregulation of Foxf1 was signi cantly correlated with a poorer prognosis for patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 49%
“…DNA hypermethylation of the CLDN1 promoter represses lung cancer stem cell-like phenotype and enhances chemotherapeutic efficacy [ 39 ]. However, hypomethylation of FOXF1 facilitates cell proliferation, acquires cancer stem properties, and inhibited cell apoptosis to induce cisplatin resistance in NSCLC [ 36 ]. Here, we demonstrated DNMT3A-mediated SFRP1 methylation promoted tumor progression in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…Since epigenetic alterations have been found to contribute the programing of the stem cells that causes normal stem cells to CSCs with loss of the multilineage differentiation potential and maintain the stem-like properties such as selfrenew, proliferation, and invasion of distal tumor sites [33]. Epigenic modification such as DNA methylation and histone methylation reprogram CSCs contributes to multiple cancer initiation, progression, and therapy responses [34][35][36]. DNA methylation is a pivotal mechanism in cancer that regulate gene expression and cell fate commitment [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Although cisplatin or cis-diamminedichloroplatinum (II) has been widely used as a first-line platinum based-chemotherapy for lung cancer patients [ 71 ], eventual drug resistance and cancer relapse severely limit clinical benefit [ 72 , 73 ]. The subpopulation of CSCs in tumors are recognized contributors to cisplatin resistance in lung cancer [ 23 , 74 , 75 ]. The promising CSC-targeting activity of jorunnamycin A was demonstrated by its enhancement of cisplatin-induced apoptosis in CSC-enriched spheroids ( Figure 8 C,D).…”
Section: Discussionmentioning
confidence: 99%